A Highly Sensitive, Reliable, and High‐Temperature‐Resistant Flexible Pressure Sensor Based on Ceramic Nanofibers. Issue 17 (27th July 2020) - Fu, Min; Zhang, Jianming; Jin, Yuming; Zhao, Yue; Huang, Siya; Guo, Chuan Fei
Abstract: Flexible pressure sensors are essential components for soft electronics by providing physiological monitoring capability for wearables and tactile perceptions for soft robotics. Flexible pressure sensors with reliable performance are highly desired yet challenging to construct to meet the requirements of practical applications in daily activities and even harsh environments, such as high temperatures. This work describes a highly sensitive and reliable capacitive pressure sensor based on flexible ceramic nanofibrous networks with high structural elasticity, which minimizes performance degradation commonly seen in polymer‐based sensors because of the viscoelastic behavior of polymers. Such ceramic pressure sensors exhibit high sensitivity (≈4.4 kPa −1 ), ultralow limit of detection (<0.8 Pa), fast response speed (<16 ms) as well as low fatigue over 50 000 loading/unloading cycles. The high stability is attributed to the excellent mechanical stability of the ceramic nanofibrous network. By employing textile‐based electrodes, a fully breathable and wearable ceramic pressure sensor is demonstrated for real‐time health monitoring and motion detection. Owing to the high‐temperature resistance of ceramics, the ceramic nanofibrous network sensor can function properly at temperatures up to 370 °C, showing great promise for harsh environment applications. Abstract : A highly sensitive and reliable pressure sensor based on flexible ceramic nanofibrous networks is designed in an extra lightweight, compliant, and breathable form, which is demonstrated to be suitable for continuous health monitoring and motion detection during long‐term wearing. Moreover, the sensor can function properly under high temperatures, showing great promise for applications under extreme conditions.